2014
DOI: 10.1111/jhn.12227
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the best method to estimate the energy density of a population using food purchase data

Abstract: Because the World Cancer Research Fund recommendations are based on ED from food and milk, it was considered prudent to use this method for policy purposes and for future monitoring work of the Scottish Diet to ensure consistency of reporting and comparability with other published studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…While energy intakes and percentage of energy from fat are similar across the social gradient, there is a significant difference in energy density calculated from foods and milk (29) . This may be due to less deprived households consuming a greater weight of food but with the same overall energy and fat composition (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…While energy intakes and percentage of energy from fat are similar across the social gradient, there is a significant difference in energy density calculated from foods and milk (29) . This may be due to less deprived households consuming a greater weight of food but with the same overall energy and fat composition (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…ED (overall and by quintile) of the Scottish diet was estimated for each of the ED methods employed, and data were examined by year, deprivation category and HH composition. The results of this review are reported in a further paper ( 46 ) , but it was concluded that food and milk (718 kJ/100 g) was the most accurate reflection of all food consumed. As it is not possible to distinguish between milk purchased as a drink and milk incorporated into foods (e.g.…”
Section: Methodsmentioning
confidence: 89%
“…Kant & Graubard ( 42 ) also reported an association between higher income and lower ED as did Nichèle et al ( 44 ) and Ricciuto & Tarasuk ( 45 ) who calculated the ED of diets in French and Canadian populations, respectively. Wrieden et al ( 46 ) explored the possible ways by which ED of the Scottish diet could be calculated using the UK Expenditure and Food Survey (EFS)/UK Living Costs and Food Survey (LCF), and concluded that calculating ED from the food and milk consumed as reported by Prentice & Jebb ( 41 ) and used by the WCRF ( 6 ) (M Wiseman, personal communication) was prudent to ensure consistency of reporting and allow comparisons with previously reported dietary ED.…”
mentioning
confidence: 99%
“…Electronic scales and training were provided to ensure detailed descriptions, and consumed weights of foods and beverages were reported. Energy density was calculated from the contribution of all food and milks (excluded all other drinks) (total EI divided by total weight intake) based on criteria previously used ( 35 ).…”
Section: Methodsmentioning
confidence: 99%